Deterioration of mitochondrial bioenergetics and ultrastructure impairment in skeletal muscle of a transgenic minipig model in the early stages of Huntington's disease - Rodinova, Marie; Krizova, Jana; Stufkova, Hana; Bohuslavova, Bozena; Askeland, Georgina; Dosoudilova, Zaneta; Juhas, Stefan; Juhasova, Jana; Ellederova, Zdenka; Zeman, Jiri; Eide, Lars; Motlik, Jan; et al. (Disease models & mechanisms, 2019)
Skeletal muscle wasting and atrophy is one of the more severe clinical impairments resulting from the progression of Huntington's disease (HD). Mitochondrial dysfunction may play a significant role in the etiology of HD, but the specific condition of mitochondria in muscle has not been widely studied during the development of HD. To determine the role of mitochondria in skeletal muscle during the early stages of HD, we analyzed quadriceps femoris muscle from 24-, 36-, 48- and 66-month-old transgenic minipigs that expressed the N-terminal portion of mutated human huntingtin protein (TgHD) and age-matched wild-type (WT) siblings. We found altered ultrastructure of TgHD muscle tissue and mitochondria. There was also significant reduction of activity of citrate synthase and respiratory chain complexes (RCCs) I, II and IV, decreased quantity of oligomycin-sensitivity conferring protein (OSCP) and the E2 subunit of pyruvate dehydrogenase (PDHE2), and differential expression of optic atrophy 1 protein (OPA1) and dynamin-related protein 1 (DRP1) in the skeletal muscle of TgHD minipigs. Statistical analysis identified several parameters that were dependent only on HD status and could therefore be used as potential biomarkers of disease progression. In particular, the reduction of biomarker RCCII subunit SDH30 quantity suggests that similar pathogenic mechanisms underlie disease progression in TgHD minipigs and HD patients. The perturbed biochemical phenotype was detectable in TgHD minipigs prior to the development of ultrastructural changes and locomotor impairment, which become evident at the age of 48 months. Mitochondrial disturbances may contribute to energetic depression in skeletal muscle in HD, which is in concordance with the mobility problems observed in this model.This article has an associated First Person interview with the first author of the paper.
Keywords: energetický metabolismus; prasata; Swine; modely nemocí na zvířatech; mutace; Skeletal muscle; protein huntingtin; progrese nemoci; Biomarkers; Oxidative Phosphorylation; Huntingtonova nemoc; Huntingtin Protein; HD large animal model; Mitochondria, Muscle; Muscle, Skeletal; Disease development; transport elektronů; Disease Progression; Swine, Miniature; Huntington Disease; mitochondriální proteiny; Huntington's disease; Body Weight; svalové mitochondrie; kosterní svaly; Animals, Genetically Modified; Electron Transport; Mitochondrial Proteins; Mitochondrial function; Animals; lidé; Energy Metabolism; Ultrastructure; Humans; zvířata; Disease Models, Animal; DNA; Mutation; geneticky modifikovaná zvířata; tělesná hmotnost; oxidativní fosforylace; miniaturní prasata